Morbidity and mortality associated with performing bone marrow aspiration and biopsy (2018)
Background: Bone marrow aspiration and biopsy are diagnostic methods in the study of hematological diseases. Complications are rare. Knowing the morbidity and mortality related to the procedure is essential in order to implement preventive behaviors and improvement plans. Objective: To determine the incidence of complications in patients over 18 years who were undergone to bone marrow biopsy and aspiration in a university hospital between October 2013 and May of 2015. Furthermore, frequency, socio-demographic and clinical characteristics were established as well. Materials & methods: Observational, descriptive and retrospective study. The unit of analysis was biopsies and bone marrow aspirations. The information was obtained from the database of outpatient hematology ward, into the program Group of Education and Monitoring of Egress (GESE) of the Hematology Service of Hospital de San José (Bogotá, Colombia), and from medical records. Results: A total of 1252 bone marrow aspirates and biopsies were performed on 914 patients. Seventy-seven complications were reported, which corresponds to 6.15% of all documented procedures. The most frequent complication was: pain (100%), being more affected the women (66%), OR 1,91(IC 1,18-3,11) p=0,003. Regard to pathology diagnosis, 53.2% of biopsies were histologically normal hematopoiesis, followed by 16.8% for chronic myeloproliferative syndromes, which was the diagnosis most commonly associated with bleeding events (40%):OR 8,9 (IC 1,2-66,44) p=0,006, and death (1.3%). Conclusion: Pain was the most frequently reported complication, and among bleeding complications, chronic myeloproliferative disorders were the most common diagnosis. The largest number of complications in women may be related to the anatomical differences between the genders. It is recommended to improve post-procedure analgesia and prospective studies to establish association between complications and diagnosis.